Pengaruh Kewajaran Harga dan Perkembangan Harga terhadap Kepuasan Pelanggan Pembelian Sepeda Motor Yamaha Vixion pada Dealer Lautan Teduh di Purbolinggo - Arlin, Deni Vavi; Imantoro, Jati (Jurnal Manajemen DIVERSIFIKASI, 2021)
Based on the results of the pre-survey, what became a phenomenon in this study was that there were still customers who were dissatisfied with the fairness of prices and price developments at Lautan Teduh Purbolinggo Dealers. In connection with these problems, the formulation of the problem in this study is "How much influence is fairness and price developments simultaneously affect customer satisfaction?". From these problems, the purpose of this study is to determine whether reasonableness and price developments simultaneously affect customer satisfaction. The method used in this research is the explenatory survey method, which is a survey used to explain the causal relationship between two variables through hypothesis testing which is formulated or often referred to as explanatory research. The data analysis technique used in this research is simple linear regression, partial t test, and r2 determination. Based on data analysis performed using a simple linear regression formula, it is obtained y '= 3.982 + 0.678X1 + 0.292X2 + e. Furthermore, it will be proven by the calculation of data analysis, namely the value of t and t table, the value of t count X1 is 5.995, which means that Tcount > T table (5.995> 1,670) with a significance level of 0.000 ≤ 0.05. While the value of Tcount X2 is 2,629, which means that T count > T table (2,629> 1,670) with a significance level of 0.011 ≤ 0.05. The R2 (R Square) test results obtained 0.778 or 77.8%, which means that customer satisfaction is influenced by the reliability variable, the remaining 22.2% is influenced by other factors not examined in this study. Thus, it is concluded that H1is accepted, which means that reliability in service quality has a positive and significant effect on customer satisfaction.